Mesenchymal stromal cells can be applied to red blood cells storage as a kind of cellular additive. Issue 5 (19th September 2017) - Chen, Yaozhen; Zhang, Jing; Gu, Shunli; Yin, Dandan; An, Qunxing; An, Ning; Weng, Lihong; Yi, Jing; Xu, Jinmei; Yin, Wen; Hu, Xingbin
Abstract : During storage in blood banks, red blood cells (RBCs) undergo the mechanical and metabolic damage, which may lead to the diminished capacity to deliver oxygen. At high altitude regions, the above-mentioned damage may get worse. Thus, more attention should be paid to preserve RBCs when these components need transfer from plain to plateau regions. Recently, we found that mesenchymal stromal cells (MSCs) could rescue from anemia, and MSCs have been demonstrated in hematopoietic stem cells (HSCs) transplantation to reconstitute hematopoiesis in vivo by us. Considering the functions and advantages of MSCs mentioned above, we are trying to find out whether they are helpful to RBCs in storage duration at high altitudes. In the present study, we first found that mice MSCs could be preserved in citrate phosphate dextrose adenine-1 (CPDA-1) at 4 ± 2°C for 14 days, and still maintained great viability, even at plateau region. Thus, we attempted to use MSCs as an available supplement to decrease RBCs lesion during storage. We found that MSCs were helpful to support RBCs to maintain biochemical parameters and kept RBCs function well on relieving anemia in an acute hemolytic murine model. Therefore, our investigation developed a method to get a better storage of RBCs through adding MSCs, which may be applied in RBCs storage as a kind of cellular additive into preservation solution.